A Novel Voltammetric Approach For The Quantification of Aflatoxin B1 Using a Bismuth-Modified Electrode - Hernández-Hernández, Aldahir A.; Castañeda-Ovando, Araceli; Mendoza-Huizar, Luis H.; Franco-Guzmán, Miriam; Meneses-Pimentel, Karla X.; Galán Vidal, Carlos A.; Páez-Hernández, María E.; Álvarez Romero, G. A. (Journal of the Electrochemical Society, 2021)
Aflatoxins are high-toxic secondary metabolites of Aspergillus fungus, which contaminate food at trace levels. Promising voltammetric methods were developed using mercury electrodes, however, they have negative effects on the environment. This work proposes the development and optimization of a differential pulse voltammetric methodology for the quantification of Aflatoxin B1 through bismuth film electrodes by the reduction of aflatoxin. Aflatoxin B1 reduction is controlled by its diffusion towards the electrode's surface. Optimal conditions for the preparation of the bismuth film and differential pulse voltammetry were obtained by Box-Behnken experimental designs, considering the maximization of the Aflatoxin B1 cathodic peak current. The LOD and LOQ resulted to be 11.2 ng l−1 and 37.3 ng l−1 respectively. The values for the reproducibility and repeatability as %RSD, using a 38.46 ng l−1 solution of Aflatoxin B1 for the measurements, were 5.3% and 4.6%, respectively. The proposed methodology was statistically validated using certified Aflatoxin B1 standard solutions and milk samples successfully analyzed, demonstrating that the proposed methodology represents a novel, low-cost, environmentally-friendly approach for the quantification of Aflatoxin B1.